'The important thing, always, is to tell a good story': an interview with comic book creator Erik Larsen. Issue 4 (1st October 2016) - Klaehn, Jeffery
Abstract : Erik Larsen's career in comics spans three decades. He is the creator, writer and artist of Savage Dragon . He co-founded Image Comics in 1992 and was publisher of Image Comics from 2004 to 2008. He has also produced work for a range of titles published by DC Comics ( Doom Patrol, New Teen Titans, Teen Titans Spotlight, Adventures of Superman, The Outsiders, Aquaman ) and Marvel Comics ( Punisher, Amazing Spider-Man, Nova, The Defenders, Wolverine, Thor, Fantastic Four: The World's Greatest Comics Magazine ) over the course of his career. In this interview he discusses his influences and shares his thoughts on comic book storytelling, art and craft. Additional topics explored include narration and exposition within the context of visual storytelling; the impact of publisher 'house styles' on the aesthetics of comic art; the question of whether standard industry practices and editorial restrictions mitigate against creativity and originality; Steve Ditko's Doctor Strange and Spider-Man; Jack Kirby and the Fantastic Four; and the importance of experimentation within the medium.